Eksistensi Pementasan Topeng Sidakarya Di Tengah Pandemi Covid-19 Di Kabupaten Karangasem - Duwi Oktaviana; I Kadek Abdhi Yasa (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
The outbreak of the Covid-19 pandemic has had an impact on changes in various aspects of life and the social order of Indonesian society. In Bali the spread of this virus occurred in early March 2020 and so far it has caused quite a number of victims so that the Balinese government implements strict rules and limits various activities that involve many people. This policy has had a very extraordinary impact, namely there has been a massive change in the order of people's lives. One of these changes is felt in the cultural order where various cultural activities are stopped. Art that was originally very existent could not carry out activities as it should. Its existence decreases when traditional and cultural activities are no longer accompanied by art presentations, one of which is the Sidakarya Mask dance. This research is a field research with qualitative research type. The results of this study are: 1) the process of staging the Sidakarya Mask dance including history, performance, fashion, and the Sidakarya Mask dance ceremony; 2) The function of the Sidakarya Mask dance performance includes ritual, social, aesthetic, symbolic, entertainment, and educational functions; 3) The meaning of the Sidakarya Mask dance performance which includes sociological, symbolic, theological, balance, and philosophical meanings. The presence of the Sidakarya Mask in a religious ritual in the Hindu tradition (Bali), is an inseparable part of the sequence of religious ceremonies. Through the Sidakarya Mask dance, the public is educated to always comply with health protocols in carrying out social activities in the community. The Sidakarya Mask show during the Covid-19 pandemic still exists as part of the offering in delivering yadnya while still adhering to health protocols, maintaining distance, using masks and limiting the number of spectators present during the activity.